Pengaruh Green Marketing Strategy, Brand Image, terhadap Keputusan Pembelian dengan Peran Green Brand Knowledge Sebagai Mediasi - Martiah, Anisa; Randa, Fradya; Octaviani, Rika (Program Studi Manajemen FEBM UMRAH, 2023)
This study aims to analyze the effect of green marketing strategy, brand image, on purchasing decisions with the role of green brand knowledge as mediation. The population is consumers who buy Love, Beauty and Planet products in Bandar Lampung. The sampling technique is random sampling obtained by 205 respondents. Data analysis used SEM (Structural Equation Model) with the PLS 4 program. The data analysis used was path analysis which had previously been tested for validity, reliability, and classical assumption tests. The results showed that 1) green marketing strategy has a positive effect on purchasing decisions, 2) brand image has a positive effect on purchasing decisions, 3) Green Brand Knowledge has a positive effect on purchasing decisions, 4) Brand image has a positive effect on green brand knowledge, 5) green marketing strategy, brand image, and green brand knowledge have a positive effect on purchasing decisions